Hierarchical Analysis for Choosing a Waterproofing Alternative in Concrete Elements - مكيه, سماح (Latakia University Journal -Engineering Sciences Series, 2023)
The life span of concrete decreases when water penetrates through the pores and cracks of the concrete, carrying with it chemicals that destroy its structure and cause rusting of the reinforcing steel, so it was necessary to work to increase the impermeability of the concrete used. There were many possible methods and research developed to secure concrete waterproofing, and the effect of each one on the properties of the concrete, the life of the insulation, the cost of implementation, and so on, was different, which made it necessary to work on choosing the best method for securing impermeability. In this research, a methodology has been proposed that can be applied based on research laboratory experiments to be employed later to serve the practical reality. This methodology differentiates between waterproofing solutions (increasing the impermeability by increasing the caliber of concrete, insulation by adding special polymers to the mixture, insulation with asphalt rollers, rubber insulation for roofs) using AHP hierarchical analysis to find the alternative The best for the studied concrete structure according to several criteria (resistance to pressure, resistance to acidic media, permeability, insulation life, cost) with the ability of this methodology to add new alternatives in line with continuous laboratory results and has the ability to add other criteria. Simple pressure, permeability and resistance tests were performed on acidic media for three types of concrete samples: a 350 kg/m3 concrete samples considered as the reference sample, a 350 kg/m3 concrete samples with 5% SBR by weight of cement and a 450 kg/m3 concrete samples without addition. The results of the tests were used to determine the matrices of the relative importance of the alternatives for each criterion for the hierarchical analysis to choose the best alternative. his methodology was applied to the two cases of study, the first is a concrete water tank and the second is the last roof of a residential building; The Expert Choice program was used to select the best alternative in each case, so insulation by adding SBR to the mixture was the best alternative in the first case, and rubber insulation was the best alternative in the second case.